Telegram and IS: A Potential Security Threat? - Leong, Dymples (2015)
The removal of 164 Islamic State-related channels on Telegram highlights the savviness of the group in the usage of encrypted and secure messaging applications, and also draws to attention the difficulties of governments in balancing the right of privacy and the security capabilities of preventing attacks against countries.